Burkholderia BcpA mediates biofilm formation independently of interbacterial contact‐dependent growth inhibition. Issue 6 (16th August 2013) - Garcia, Erin C.; Anderson, Melissa S.; Hagar, Jon A.; Cotter, Peggy A.
Summary: Contact‐dependent growth inhibition (CDI) is a phenomenon in which Gram‐negative bacteria use the toxic C‐terminus of a large surface‐exposed exoprotein to inhibit the growth of susceptible bacteria upon cell–cell contact. Little is known about when and where bacteria express the genes encoding CDI system proteins and how these systems contribute to the survival of bacteria in their natural niche. Here we establish that, in addition to mediating interbacterial competition, the B urkholderia thailandensis CDI system exoprotein BcpA is required for biofilm development. We also provide evidence that the catalytic activity of BcpA and extracellular DNA are required for the characteristic biofilm pillars to form. We show using a bcpA – gfp fusion that within the biofilm, expression of the CDI system‐encoding genes is below the limit of detection for the majority of bacteria and only a subset of cells express the genes strongly at any given time. Analysis of a strain constitutively expressing the genes indicates that native expression is critical for biofilm architecture. Although CDI systems have so far only been demonstrated to be involved in interbacterial competition, constitutive production of the system's immunity protein in the entire bacterial population did not alter biofilm formation, indicating a CDI‐independent role for BcpA in this process. We propose, therefore, that bacteria may use CDI proteins in cooperative behaviours, like building biofilm communities, and in competitive behaviours that prevent non‐self bacteria from entering the community.